(untitled) ("Conference on Universal Science Research 2023", 2025)
Benzene-1,4-dicarboxylic acid (phthalic acid) is a strong acid and an important raw material for many industrial products, widely used in plastics, paints, pharmaceuticals and many other industries. There are many methods available for its synthesis and properties, further increasing the industrial importance of this compound.